Pelatihan “Artificial Intelligence for Kids” bagi Tenaga Pendidik di Sekolah Dasar Muhammadiyah Danaraja: Training on “Artificial Intelligence for Kids” for Educators at Muhammadiyah Danaraja Elementary School - Fitriani, Maulida Ayu; Nurlina, Laily; Febrianto, Dany Candra (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The artificial intelligence (AI) training program for teachers focused on developing animation-based teaching media that integrates AI concepts. This training produced dynamic and reusable instructional materials, enabling teachers to reintroduce the content effectively to students. By helping educators incorporate AI into their lessons, the program aims to prepare the younger generation to understand, manage, and actively participate in an increasingly advanced digital world, supporting government efforts to enhance national competitiveness. Through this training, teachers learned to embed AI concepts into various subject areas. Examples of the resulting teaching media include applications for animal recognition, growth stages, Arabic vocabulary, and more. The platforms used for media development included Pose Block from media.mit.edu and Teachable Machine by Google. The satisfaction survey revealed that 74.5% of participants rated the training as very satisfactory.